Richard Rolle - Karáth, Tamás (Brepols, 2018)
This book explores the fifteenth-century translations of Richard Rolle’s Latin and English writings into English and Latin, respectively, raising questions about the impact of translation on an author’s legacy through the editorial activity of his translators. The volume also discusses Rolle’s sensory mysticism - which was criticized by the ensuing generation of mystics - whilst looking into the ways in which translations of his work create a fifteenth-century version of Rolle. While the fifteenth-century translations did not represent the standard means of shaping Rolle’s authority, this study illustrates individual encounters with Rolle’s writings in which interpretation was much more overt than in the devotional reuse of untranslated Rollean material. The volume asks if alternative and perhaps controversial portraits of the same author arise from the translations. Richard Rolle has received many, often conflicting, labels in scholarship: the father of English prose, the first medieval English author, the first known mystic of English literature, the runaway Oxford man, the non-conformist hermit, and the misogynist. This book is located in the context of the late medieval censorship culture which inevitably impacted the translators’ treatment of authority, revelatory writing, and theological speculations. The analysis of Rolle in translation highlights the various meanings, practices, and implications of translation in the fifteenth century.